BSA and DNA Binding Studies of Aspergillus foetidus Mediated Biosynthesized CdS Nanoparticles - Nasrin, Tina; Sadhukhan, Ratan; Kumar Das, Tapan (Current Nanoscience, 2016)
Background: Instead of traditional antibiotics, antimicrobial property of nanoparticle has been documented in various research reports. In such cases, nanoparticle mainly interacts with proteins and DNA like macromolecules. But still the mechanism of anti-microbial activity of CdS nanoparticles is partially known. Methods: We have synthesized CdS nanoparticles by using Aspergillus foetidus (MTCC8876). Our process for synthesis of nanoparticle is hazard free as well as economic. To investigate the mode of interaction between CdS nanoparticles and BSA, a number of photo- and fluorometric analyses were considered. Furthermore, DNA (calf thymus DNA) binding ability of CdS nanoparticles was also studied through photo- and fluorometric analyses and viscosity measurement. Results: About 10-15 nm of stable CdS nanoparticle has been synthesized by Aspergillus foetidus. Our results ascertained that CdS nanoparticles interact with BSA (binding constant, K=13.8 104M−1) and DNA (binding constant, K=10.47 102M−1) successively. Conclusion: Aspergillus foetidus mediated biosynthesized CdS nanoparticles effectively interact with BSA and calf thymus DNA.
Keywords: Protein